2021
DOI: 10.1177/23780231211005216
|View full text |Cite
|
Sign up to set email alerts
|

What Can Sociology Say About Grit? A Cross-Cultural Exploration of the Relationships between Socioeconomic Status, Sense of Control, and Grit

Abstract: Despite growing interest from the public, little attention has been directed toward grit in sociology. By disaggregating grit into its component factors (i.e., perseverance of effort and consistency of interest) on the basis of a measurement test, the author examines the potentially contrasting relations of grit to socioeconomic status. Using survey data from the United States and South Korea, the author finds that those with higher socioeconomic status partially translate their structural advantages into grit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Parental education is also correlated with kindergarten students' persistence level (Sutter et al, 2022). In contrast, Kwon found that parents' education levels were negatively associated with student consistency in the United States and South Korea (Kwon, 2021).…”
Section: Introductionmentioning
confidence: 91%
“…Parental education is also correlated with kindergarten students' persistence level (Sutter et al, 2022). In contrast, Kwon found that parents' education levels were negatively associated with student consistency in the United States and South Korea (Kwon, 2021).…”
Section: Introductionmentioning
confidence: 91%